2020
DOI: 10.1002/jbmr.4754
|View full text |Cite
|
Sign up to set email alerts
|

PPI-Induced Changes in Plasma Metabolite Levels Influence Total Hip Bone Mineral Density in a UK Cohort

Abstract: Proton pump inhibitors (PPIs) are among the most used drugs in the UK. PPI use has been associated with decreased bone mineral density (BMD) and increased fracture risk, although these results have been inconsistent. We hypothesized that PPI could modulate BMD by altering gut and/or host systemic metabolic environments. Using data from more than 5000 British male and female individuals, we confirmed that PPI use is associated with decreased lumbar spine and total hip BMD. This effect was not mediated through t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 68 publications
0
1
0
Order By: Relevance
“…Gastric acids are important for the absorption of multiple nutrients including vitamins and calcium 8 . Other mechanisms may be involved, and Zhang et al used a large cohort of patients in the United Kingdom to examine the possibilities 9 . Using data on 14,000 combined male patients and female patients, the investigators confirmed that proton pump inhibitor use was associated with decreased BMD of the spine and total hip regions of analysis.…”
Section: Fracture Riskmentioning
confidence: 99%
“…Gastric acids are important for the absorption of multiple nutrients including vitamins and calcium 8 . Other mechanisms may be involved, and Zhang et al used a large cohort of patients in the United Kingdom to examine the possibilities 9 . Using data on 14,000 combined male patients and female patients, the investigators confirmed that proton pump inhibitor use was associated with decreased BMD of the spine and total hip regions of analysis.…”
Section: Fracture Riskmentioning
confidence: 99%
“…Maes et al [ 14 ] showed that long-term PPI use in patients older than 60 years increased the incidence of fractures due to osteoporosis. Zhang et al [ 48 ] reported PPI use may influence total hip bone mineral density via plasma metabolites involved in the sex hormone pathway. The FDA has stated that low-dose, short-term oral PPIs are not associated with fractures; moreover, fracture warnings owing to high-dose, long-term PPIs are still present in the FDA’s current safety announcement [ 49 ].…”
Section: Discussionmentioning
confidence: 99%